ANALISIS KEPUASAN PENUMPANG TERHADAP PELAYANAN BUS SEKOLAH KOTA SURABAYA DENGAN METODE IMPORTANT PERFORMANCE ANALYSIS - Boy Dian Anugra Sandy Anugra Sandi (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2019)
The Department of Transportation in Surabaya City provides school bus services. Buses are designed to accommodate students departure to school. Bus routes are optimized to reach schools located on the main streets of Surabaya. There are 12 public / private junior high schools, 11 public / private senior high schools, and 8 public / private vocational high schools that are passed by the route. The number of buses available is 4 units with medium capacity. This bus has a route from Dukuh Menanggal Street to Prof. Dr. Moestopo Street. This study aims to determine the level of user satisfaction with school bus services so that the school bus can be optimized for its facilities and services. Data collection was carried out by means of questionnaire surveys. Comfort, security, convenience, trajectory, and vehicle are the service variables measured. The data obtained is then analyzed by the IPA method which results in 4 assessment quadrants. The results obtained from the Customer Satisfaction Index (CSI) obtained are 0.9157, where customer satisfaction is included in the criteria 0.80 - 1.00.Keywords: School Bus, Bus Service, Satisfaction Analysis